2005
DOI: 10.1149/1.2048140
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Morphological Characterization of Pt–Cu Dealloying

Abstract: The results of morphological and electrochemical characterizations of Cu 0.8 Pt 0.2 , Cu 0.75 Pt 0.25 , and Cu 0.71 Pt 0.29 dealloying in 1 M H 2 SO 4 are presented. The critical potential values for these systems were measured and compared to previously reported results for the Ag-Au system. The differences between the systems are discussed in terms of their relative surface diffusivity values. Based on potential hold data, the dealloying critical potentials for Cu 0.8 Pt 0.2 , Cu 0.75 Pt 0.25 , and Cu 0.71 P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
94
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 23 publications
10
94
0
Order By: Relevance
“…Moreover, the entire alloy surface in Cu-30Zr alloy becomes unstable and shows extensive transgranular and intergranular cracking. Pugh et al have observed this phenomenon of the crack after the dealloying behavior in Pt-Cu alloy [8]. When applying −0.1 V anodic potential, some phases are removed from the electrode surface resulting in the formation of holes.…”
Section: Comparison Of the Corrosion Morphologies Of Three Cu-zr Allomentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, the entire alloy surface in Cu-30Zr alloy becomes unstable and shows extensive transgranular and intergranular cracking. Pugh et al have observed this phenomenon of the crack after the dealloying behavior in Pt-Cu alloy [8]. When applying −0.1 V anodic potential, some phases are removed from the electrode surface resulting in the formation of holes.…”
Section: Comparison Of the Corrosion Morphologies Of Three Cu-zr Allomentioning
confidence: 96%
“…Dealloying is a corrosion process whereby one or several electronegative constituents of an alloy are preferentially removed from the alloy due to their high reactivity, leading to an altered residual structure [1][2][3][4][5][6][7][8]. Today, it is widely recognized that dealloying phenomena play an important role in many alloys, for example, in the corrosion of brass [9], stainless steel [10,11], the aluminum alloy 2024 [12], and the high-Pd dental alloys [13].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most widespread method of nanoporous metal structures formation is dealloying process, which consist in selective chemical or electrochemical etching of a desired component from its alloy [29][30][31][32][33][34]. Also porous metal nanosystems can be synthesized using a template with desired pore structure.…”
Section: Introductionmentioning
confidence: 99%
“…8,9) Figure 1(a) shows the microstructure of the dealloyed nanoporous Pt. The ligament size of the nanoporous Pt was $3 nm.…”
Section: Methodsmentioning
confidence: 99%